Uplink User Signal Separation for OFDMA-Based Cognitive Radios. (13th December 2009) - Şahin Şahin, Mustafa E. Mustafa E.; Guvenc Guvenc, Ismail Ismail; Arslan Arslan, Hüseyin Hüseyin
Abstract : Spectrum awareness of orthogonal frequency division multiple access- (OFDMA-) based cognitive radios (CRs) can be improved by enabling them to separate the primary user signals in the uplink (UL). Assuming availability of information about the basic parameters of the primary system as well as time synchronization to the first arriving user signal, two algorithms are proposed in this paper. The first one targets estimating the size of the frequency allocation block of the primary system. The performance of this algorithm is compared with the results of a Gaussian approximation-based approach that aims to determine the probability of correct block size estimation theoretically. The second one is a semiblind user separation algorithm, which estimates the carrier frequency offsets and time delays of each block by exploiting the cross-correlations over pilot subcarriers. A two-dimensional clustering method is then employed to group the estimates, where each group belongs to a different user. It is shown that the proposed algorithms can improve the spectrum opportunity detection of cognitive radios. Feasibility of the algorithms is proved through practical simulations.